Methicillin resistant Staphylococcus aureus adhesion to human umbilical vein endothelial cells demonstrates wall shear stress dependent behaviour - Viegas, K.; Dol, Sharul sham; Salek, M.; Shepherd, R.; Martinuzzi, R.; Rinker, K. (2011)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is an increasingly prevalent pathogen capable of causing severe vascular infections. The goal of this work was to investigate the role of shear stress in early adhesion events.Methods: Human umbilical vein endothelial cells (HUVEC) were exposed to MRSA for 15-60 minutes and shear stresses of 0-1.2 Pa in a parallel plate flow chamber system. Confocal microscopy stacks were captured and analyzed to assess the number of MRSA. Flow chamber parameters were validated using micro-particle image velocimetry (PIV) and computational fluid dynamics modelling (CFD).Results: Under static conditions, MRSA adhered to, and were internalized by, more than 80% of HUVEC at 15 minutes, and almost 100% of the cells at 1 hour. At 30 minutes, there was no change in the percent HUVEC infected between static and low flow (0.24 Pa), but a 15% decrease was seen at 1.2 Pa. The average number of MRSA per HUVEC decreased 22% between static and 0.24 Pa, and 37% between 0.24 Pa and 1.2 Pa. However, when corrected for changes in bacterial concentration near the surface due to flow, bacteria per area was shown to increase at 0.24 Pa compared to static, with a subsequent decline at 1.2 Pa.Conclusions: This study demonstrates that MRSA adhesion to endothelial cells is strongly influenced by flow conditions and time, and that MSRA adhere in greater numbers to regions of low shear stress. These areas are common in arterial bifurcations, locations also susceptible to generation of atherosclerosis. © 2011 Viegas et al; licensee BioMed Central Ltd.